The association of temporomandibular Joint dysfunction with the cervical spine pain - Ghauri, Muhammad Waqas; Rao, Nosheen; Shabana Rahim; Amna Batool Naz; Nasir Mehmood (Journal of University Medical & Dental College, 2023)
ABSTRACT Background Temporo-mandibular dysfunction” is a terminology that is used to refer a broad/wide range of interconnected conditions which affecting the temporo-mandibular joint, muscles involve in the process of chewing, and clogging up of the joint. Cervical spine dysfunction is related with the temporomandibular joint dysfunction. Objective To find out the association of temporomandibular joint dysfunction with the cervical spine pain. Methodology The study, conducted at Gardezi Lab and Clinic, involved 145 participants aged 18-30, with 145 samples in 3 months ranges February 09 to May 09, 2023 after the approval of research study from Ethical research committee. Numeric Pain Rating Scale and Questionnaire form for TMD were used. Results were analyzed using SPSS version 22, and interpreted using frequency and tables. Results The test statistics of the cervical spine pain and chewing difficulty, uncomfortable bite, temple pain, and noises from the dysfunctional jaw (a = 10.898, a = 35.446, a = 18.813, and a = 14.345 respectively) have a p value of 0.000, which was less than the normal and standard p value of 0.05. So there is association present between neck pain and chewing difficulty, uncomfortable bite, temple pain and noises from the dysfunctional jaw. Conclusion This study concluded that there is positive association between the pain in the cervical-region and resistance in chewing, uncomfortable feelings during bite, pain in the temple region, and noises from the jaw. But there is negative association present between the neck pain and locking sensation of the jaw. Key Words Cervical Spine, Temporo-mandibular Dysfunction